Red photoluminescent PMMA nanohybrid films for modifying the spectral distribution of solar radiation inside greenhouses. (January 2016) - El-Bashir, S.M.; Al-Harbi, F.F.; Elburaih, H.; Al-Faifi, F.; Yahia, I.S.
Abstract: Luminescent solar concentrator (LSC) films based on Polymethylmethacrylate (PMMA) nanohybrids were prepared using free radical polymerization of MMA incorporated with oxide nanoparticles; SiO2, ZnO and TiO2 . The effect of nano-oxide type was studied by Fourier transform infrared spectroscopy (FT-IR), UV–Vis absorption and fluorescence spectroscopy measurements. The performance of LSC nanohybrid films was evaluated and optimized for photoselective greenhouse cladding applications in order to increase the plant productivity by changing the solar spectrum. It was found that ZnO nanohybrid LSC film had offered the best spectral properties for photosynthetic active radiation besides their excellent resistance to photo and thermal degradation especially in hot countries like KSA. Regarding thermal efficiency, the highest infrared (IR) efficiency has been found for silica nanohybrid LSC film, which reached about 83%. This result is promising to improve thermal efficiency in greenhouse claddings in cold regions and thermal covering systems like solar dryers and solar desalination systems. Graphical abstract: Uniform light scattering by LSC greenhouse films based on PMMA nanohybrid LSC films. Highlights: Fluorescent dye doped PMMA nanohybrids based on oxide nanoparticles were prepared. ZnO based nanohybrids showed excellent spectral features as Photoselective greenhouse claddings. Silica based nanohybrids acquired the maximum thermal efficiency for solar desalination applications.